Stability of the Factor Structure of the Job Descriptive Index - Jung, Kenneth G.; Dalessio, Anthony; Johnson, Steven (Academy of Management Journal, 1986)
In this article the authors discuss research they conducted that examined the Job Descriptive Index (JDI) in terms of its accuracy in measuring job satisfaction. The JDI test is designed to measure five aspects related to job satisfaction which include satisfaction with supervision, co-workers, pay, promotional opportunities and the work itself. The authors were interested in how reliable the test was across a wide range of job situations and to do this they examined how accurate the five factors identified by the test measure satisfaction. They also suggest more specific subdivisons where they deem it necessary. They conclude that the five factors represent an accurate measurement of job satisfaction; however, they do provide a discussion on some items that could be revised.